Organ Donation among Malaysian Muslims: The Role of Mosques - Tumin, M.; Raja Ariffin, R.N.; Satar, N.M.; Abdullah, N.; Adnan, W.A.H.W.M.; Ismail, A.Z.; Che Soh, M. (Springer Verlag (Germany), 2015)
Background: Malaysia, a country of Muslim majority, is suffering from a severe organ shortage due to the lack of donors. Mosques are the main gateways into the Muslim community. Hence, it is imperative to explore their role in facilitating organ donation. Material/Methods: A self-administered survey was conducted between October and December 2013. We distributed 700 pilottested questionnaires to 82 mosques in Kuala Lumpur and its suburbs. The respondents were stratified into 2 groups: the mosque committees and the Muslim Jama’ah (individuals who come regularly to mosque for prayer). Results: Data collected from a survey on 653 Malaysian Muslims reveals that the main factors that hamper organ donation-related activities at the mosques in Malaysia are the lack of experts and financial resources. The level of autonomy of the mosque is also another main issue. The respondents believe that talks and dialogues are the best methods for organ donation campaigns at the mosques. Conclusions: We argue that if the mosques are to play a role in imparting knowledge on organ donation, there should be ample opportunity for the mosque committee to choose the content of religious talks held in their community. The mosques in Malaysia are not sufficiently facilitated to channel the information on organ donation to the Muslim community. Providing financial support and expert campaigners are expected to increase organ donation-related activities at the mosques and subsequently could increase awareness regarding organ donations among Malaysian Muslims.